Penerapan Gaya Servant Leadership (Studi: Mon Cheri Ice Cream, Bakery, Cafe) - Sharmilee Nanda; Leonard Adrie Manafe (Majalah Ilmiah DIAN ILMU, 2022)
This study aims to determine the extent to which the servant leadership style is applied in Mon Cheri Ice Cream, Bakery, and Café companies. This study uses a qualitative method with descriptive analysis. The research approach is a case study that examines a particular case in a context or real life. The research informants were five people who were shop employees. Primary and secondary data sources were used in this study. Primary data were collected directly to communicate with the main source of research, namely shop employees as research informants. Meanwhile, secondary data was taken to support research in the form of company history, literature sources (books and similar research journals). Data collection techniques used in-depth interviews, direct field observations, and documentation. The results show that the Mon Cheri leader has not fully implemented all dimensions of servant leadership. The dimension that has not yet been fully implemented is the importance of common interests. This is due to clashing company policies that still need further study so that employee welfare is still minimal. Almost all Mon Cheri leaders have dimensions related to leadership competencies, including broad knowledge and insight, comprehensive experience, the ability to manage the company, the ability to lead a team.